2017
DOI: 10.1007/s00508-017-1259-y
|View full text |Cite
|
Sign up to set email alerts
|

Facial nerve palsy secondary to Epstein–Barr virus infection of the middle ear in pediatric population may be more common than we think

Abstract: The aim of this article is to alert clinicians that AOM induced facial nerve palsy secondary to an acute EBV infection in the pediatric population is very likely more common than originally thought. To our knowledge until the present case series, only 2 cases of AOM induced facial nerve palsy secondary to an acute EBV infection have been reported and no cases of EBV infection proven by the ISH technique showing the presence of EBV-specific RNA sequences in patient's tissue biopsies have been reported until now. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…EBV has been described in the literature as a possible causative agent of such a clinical picture, although there are in fact scant references for this virus actually being detected and identified as the causative agent in either pediatric or adult cases. Hence this case study is a valuable addition to the literature on EBV as the origin of peripheral facial paralysis [2,1517]. The patient’s recovery was slow, but positive.…”
Section: Discussionmentioning
confidence: 78%
“…EBV has been described in the literature as a possible causative agent of such a clinical picture, although there are in fact scant references for this virus actually being detected and identified as the causative agent in either pediatric or adult cases. Hence this case study is a valuable addition to the literature on EBV as the origin of peripheral facial paralysis [2,1517]. The patient’s recovery was slow, but positive.…”
Section: Discussionmentioning
confidence: 78%
“…5 Otitis media may also contribute to the development of FNP, but the pathophysiology is not well understood; Streptococcus pneumoniae and Staphylococcus species are the most likely infectious organisms. 3,6 Anatomic disruptions of the facial nerve caused by malignancies, trauma, or hypertension may also contribute to this presentation.…”
Section: Discussionmentioning
confidence: 99%
“…FNP with IM is rare in children, and although well‐recognised, the pathogenesis remains uncertain . Vogelnik et al .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Vogelnik et al reported five patients with EBV-associated FNP due to AOM. 2,3 Although no consensus has been reached regarding the ability of EBV to directly infect the middle ear cavity or introduce secondary bacterial AOM, we assert that EBV-associated FNP due to AOM might be more common than previously thought. 2,3 We hypothesise that our case was compatible with EBV-associated FNP secondary due to otomastoiditis and/or AOM.…”
Section: Key Pointsmentioning
confidence: 99%